2017
DOI: 10.1103/physrevlett.118.050501
|View full text |Cite
|
Sign up to set email alerts
|

Superdense Coding over Optical Fiber Links with Complete Bell-State Measurements

Abstract: Adopting quantum communication to modern networking requires transmitting quantum information through fiber-based infrastructure. We report the first demonstration of superdense coding over optical fiber links, taking advantage of a complete Bell-state measurement enabled by timepolarization hyperentanglement, linear optics, and common single-photon detectors. We demonstrate the highest single-qubit channel capacity to date utilizing linear optics, 1.665 ± 0.018, and we provide a full experimental implementati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 26 publications
0
88
0
Order By: Relevance
“…That is, the time interval between the wave packets of input state is adjusted to satisfy the condition of constructive interference with ωt = 2mπ (m is an integer), which has been demonstrated experimentally by Williams et al [33] In their experiment, the photon pairs prepared by SPDC are sent into an interferometer with two time delays t 0 = 5ns and t 1 = 10ns , and the time resolution for photon detectors is 4ns . That is, the time interval between the wave packets of input state is adjusted to satisfy the condition of constructive interference with ωt = 2mπ (m is an integer), which has been demonstrated experimentally by Williams et al [33] In their experiment, the photon pairs prepared by SPDC are sent into an interferometer with two time delays t 0 = 5ns and t 1 = 10ns , and the time resolution for photon detectors is 4ns .…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the time interval between the wave packets of input state is adjusted to satisfy the condition of constructive interference with ωt = 2mπ (m is an integer), which has been demonstrated experimentally by Williams et al [33] In their experiment, the photon pairs prepared by SPDC are sent into an interferometer with two time delays t 0 = 5ns and t 1 = 10ns , and the time resolution for photon detectors is 4ns . That is, the time interval between the wave packets of input state is adjusted to satisfy the condition of constructive interference with ωt = 2mπ (m is an integer), which has been demonstrated experimentally by Williams et al [33] In their experiment, the photon pairs prepared by SPDC are sent into an interferometer with two time delays t 0 = 5ns and t 1 = 10ns , and the time resolution for photon detectors is 4ns .…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In 2006, Schuck et al [25] gave the complete analysis of the four polarization Bell states in experiment with the help of the intrinsic time-energy correlation of photon pair. Recently, Williams et al [33] demonstrated an attractive protocol in experiment to completely differentiate the four polarization Bell states assisted by two time delays, where only www.advancedsciencenews.com www.ann-phys.org linear optical elements and common single-photon detectors are required. [26] with twophoton polarization-momentum hyperentanglement via linear optics.…”
Section: Doi: 101002/andp201900201mentioning
confidence: 99%
See 1 more Smart Citation
“…Different complexities to realize these measurements made a big difference between the achieved results–the Illinois experiment achieved an average successful probability of 94.8% and a capacity of 1,630(6) bits thus beating a fundamental limit of log 2 3 bits on the dense coding capacity using only linear optics for the first time, while the Tianjin experiment observed an average success probability of 82% and a capacity of 1.10(4) bits which is no better than the Innsbruck experiment . Time‐polarization hyperentanglement–based dense coding was further developed into the one using four temporal modes in the Oak Ridge experiment ( Figure ). This experiment achieved an average success probability of 95.3% and a capacity of 1.665(0.018) bits and, more importantly, paved the way for practical application of quantum dense coding for at least two reasons; first, its demonstration over optical fiber links can be easily extended to long distance communication assisted by quantum dense coding, secondly, it showed potential in hybrid quantum‐classical transfer protocols by transmitting a 3.4 kB image with 0.87 fidelity a.…”
Section: Experimental Status and Challengesmentioning
confidence: 99%
“…Apparatus of Oak Ridge experiment . Four temporal modes were used to identify four Bell states without the requirement of PNRDs.…”
Section: Experimental Status and Challengesmentioning
confidence: 99%